TECHNOLOGICAL ASPECTS OF FORMATION OF QUALITY INDICATORS OF MUFFINS WITH HIGH CONTENT OF NUTRIENTS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article presents the results of scientific research on the development of a muffin recipe using an innovative component – flour derived from the extruded kernel of sunflower seeds (BEYANS). The main objective of the study was to enhance the technological properties of the muffin production process by enriching the dough with valuable nutrients and improving its structural, mechanical, and sensory characteristics. The experimental data confirm that the incorporation of BEYANS in quantities ranging from 5% to 15% of the wheat flour mass leads to significant improvements in the physical and chemical properties of both the semi-finished dough and the final baked goods.It was observed that the use of BEYANS resulted in increased moisture retention, higher bulk mass, and improved product yield. Simultaneously, there was a noticeable reduction in density, alkalinity, and thermal processing losses. These effects are attributed to the functional composition of BEYANS, which includes a high protein content (38.73%) with a well-balanced amino acid profile, a significant proportion of soluble proteins (76.35%), and fat (4.87%) rich in unsaturated fatty acids. The additive also contains 22 essential elements (including macro-, micro-, and ultra-microelements), along with a complex of biologically active substances, such as fat- and water-soluble vitamins, and 19 amino acids (10 essential and 9 non-essential).Muffins containing BEYANS demonstrated superior organoleptic qualities, improved textural properties (lower crumbliness and compressibility), and enhanced freshness retention over 30 days of storage, compared to traditionally produced muffins. The enrichment with BEYANS contributed to a substantial increase in protein, ash, and fat contents, while reducing carbohydrate levels. Based on the results, the 10% substitution level of BEYANS for wheat flour was identified as optimal, providing a balance between technological feasibility and nutritional enhancement.The proposed formulation and production process open up possibilities for the creation of functional confectionery products aimed at targeted nutritional support. These muffins may be recommended as part of specialized diets, including those intended for military personnel, individuals with increased physical demands, or populations requiring enriched nutritional intake during periods of recovery or stress.
Keywords: muffins; BEANS; food additive; nutrients; technology; quality; dough structure; moisture-containing capacity; organoleptic indices